Independent Commisioners And Sharia Supervisory Board On Sustainable Finance On Indonesian Islamic Comersial Banks - Rosilawati, Weny; Sidik, Sofwan (Al-Mashrof: Islamic Banking and Finance, 2024)
This study aims to analyze the effect of independent commissioners, and the sharia supervisory board on the implementation of Sustainable Finance at Islamic commercial banks in Indonesia. This study uses secondary data taken from annual reports and sustainability reports of Islamic commercial banks in Indonesia during a certain period. The data analysis technique used is multiple linear regression with classical assumption test to ensure the validity of the model. The results showed that of the two variables tested, only the independent commissioner had a significant influence on the implementation of Sustainable Finance. The sharia supervisory board variable did not show a significant influence on Sustainable Finance. This finding suggests that the presence of independent commissioners in the board structure of Islamic banks plays an important role in encouraging the implementation of Sustainable Finance. The implications of this study provide input for regulators and Islamic banks to increase the role of independent commissioners as a strategic step in strengthening their commitment to Sustainable Finance.